Health Diplomacy and Global Health: Latin American perspectives - Ribeiro, Helena; Ventura, Deisy de Freitas Lima (Revista de Saúde Pública, 2019)
We will analyze and comment on the book Health Diplomacy and Global Health: Latin American Perspectives, edited by Paulo Marchiori Buss and Sebastián Tobar and published by Editora Fiocruz. Throughout its 653 pages, the book brings prominent national and foreign authors in the field of Health Diplomacy and Global Health, depicting a decade in which Brazil had great international protagonism in the field of Public Health, especially in South-South cooperation, in an innovative and structuring manner. Furthermore, the chapters present theoretical aspects and basic principles of Global Health as a new field of knowledge, in which the country has been developing and sharing scientific production with a Latin American perspective, focused on the pursuit of equity and health for all peoples of the world.